Business Ethics in North America: Trends and Challenges - Petrick, Joseph A.; Cragg, Wesley 1941-; Sañudo, Martha (2011)
Using 15 years of data (1995–2009) from literature reviews, survey questionnaires, personal interviews, and desktop research, the authors examine North American (Canada, Mexico, and the United States of America) regional trends in business ethics research, teaching and training. The patterns indicate that business ethics continues to flourish in North America with high levels of productivity in both quantity and quality of teaching, training and research publication outputs. Topics/themes that have been covered during the time period are treated with an acknowledgement of the concomitant marginal impact on improving ethical business behavior and contexts—as recurring domestic and global scandals attest. Major North American business ethics challenges/issues to be addressed in the future are identified.
Keywords: Future North American business ethics challenges; Teaching and training; Regional trends in business ethics research; North America; Business Ethics